Pengaruh Marketing Mix dan Service Quality Terhadap Consumer Satisfaction Transmart Coarrefour Grand Kawanua dan Trans Studio Mini - Wowiling, Christine Natalia; Pio, Riane J.; Kalangi, Johnny A. F (Sam Ratulangi University, 2019)
This study aims to determine the extent the influence of classic markeing mix with variable product, price, place and promotion, on consumer satisfaction and the effect of service quality on consumer satisfaction. The populations in this study were Grand Kawanua Manado Transmart Carrefour customers, amounting to 1920 people, while the number of samples was 100 respondents. This study uses a quantitative approach with SEM-PLS analysis. The resluts of the study indivate that there is an effect of marketing mix on consumer satisfaction, and service quality influencing consumer satisfaction. To maintain consumer satisfaction in the eara of very tight retail business competition, companies should continue to improve service quality to customers by paying attention to the elements of marketing mix such as determining reasonable and competitive prices, good product quality, and continuing promotion. The results of this study are expected to provide benefits for other researchers, and for practitioners in developing retail business marketing strategles.